Anorexia Nervosa, Major Depression, and Suicide Attempts: Shared Genetic Factors. Issue 5 (24th February 2016) - Thornton, Laura M.; Welch, Elisabeth; Munn‐Chernoff, Melissa A.; Lichtenstein, Paul; Bulik, Cynthia M.
Abstract : The extent to which genetic and environmental factors influenced anorexia nervosa (AN), major depressive disorder (MDD), and suicide attempts (SA) were evaluated. Participants were 6, 899 women from the Swedish Twin Study of Adults: Genes and Environment. A Cholesky decomposition assessed independent and overlapping genetic and environmental contributions to AN, MDD, and SA. Genetic factors accounted for a substantial amount of liability to all three traits; unique environmental factors accounted for most of the remaining liability. Shared genetic factors may underlie the coexpression of these traits. Results underscore the importance of assessing for signs of suicide among individuals with AN.